Characteristics and prognosis of the catecholamine induced QT prolongation syndrome. (3rd October 2022) - Gourraud, J; Le Diffon, T; Mansourati, J; Clementy, N; Thollet, A; Rajalu, A; Cotard, V; Kyndt, F; Martins, R; Sacher, F; Probst, V
Abstract: Background: We have recently demonstrated association of unexplained sudden cardiac arrest (SCA) with inheritance of catecholamine induced QT prolongation (CIQTP). Objective: We here aim to describe incidence, characteristics and prognosis of this new syndrome in young patients with unexplained SCA or their relatives. Methods: We reviewed the medical screening of all consecutive patients or their first-degree relatives explore from 2015 after the occurrence of a SCA before age 45. Structural heart disease or inherited arrhythmia diseases were excluded. A mental stress test was performed, as previously described, for each family members. All families with a positive mental stress were included in the study. Genetic screening was performed in at least one positive patient per family using targeted sequencing on a panel of 109 genes associated with inherited arrhythmias and cardiomyopathies. Results: Among 456 patients screened (24 after SCA, 432 for familial screening) of 153 families, we identified 10 families (6.5%) with a catecholamine induced QT prolongation. No mutation was identified in these families. One hundred and ten patients were screened in CIQTP families. Thirty-four patients (30.9%) presented a CIQTP (mean age 42±20 yo, 64.7% of women). Five (14.7%) patients presented with previous symptoms (including 4 syncope and 1 SCA). Two patients (5.9%) were implanted with an ICD and eleven (32.3%) were treated with beta blocker therapy mainly because of QT prolongation >500 ms after mental stress test or previous symptoms. After a 3.6±1.8 years of follow up, no sudden cardiac death nor syncope occurred on beta blocker therapy except for one patient implanted with an ICD after a SCA. Under beta blocker treatment the patient was asymptomatic for 5 years. After a suddenly stop of the beta blocker treatment, the patient underwent VF. For 3 years now the patient is asymptomatic under beta blocker treatment. Conclusions: In our experience, CIQTP families represent 6.5% of cases of unexplained SCD and suggest systematic screening with a mental stress test for family screening after the occurrence of a SCA. Beta blocker therapy is very efficient to reduce the risk of SCA. Funding Acknowledgement: Type of funding sources: None.